Structured Semiconductors in Photocatalysis - Bedia, Jorge; Belver, Carolina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Photocatalysis represents an interesting approach for different applications, with the possibility of using sunlight as a sustainable and renewable source of energy. This technology is based on the use of a semiconductor that can be excited by light with an energy higher than its band gap, inducing the formation of energy-rich electron-hole pairs that can be involved in redox reactions. Recent progress has explored the chemical nature of structured semiconductors with the object of improving their electronic and optical properties, enhancing their photoresponse under different conditions. This Special Issue collected original research papers, reviews and commentaries focused on the challenges in the design of structured semiconductors with photocatalytic applications; thus, submissions focusing on synthesis, the characterization of new photocatalysts, studies of activity and stability, and the mechanisms of photocatalytic reactions are invited for submission.